Technology and remuneration of working time : a study on paid and unpaid working time in platform work - Fernández Massi, Mariana; Longo, Julieta (2023)
In this article, we analyse platform-mediated work on the basis of the results of a qualitative study conducted in Argentina in the areas of delivery services and design. The guiding question of this research is how digital work processes change the relationship between paid and unpaid working times. To answer this question, we examine the remuneration system of two types of platforms, and we identify different forms of unpaid labour time in platform-mediated work. Two main conclusions arise from this analysis. On the one hand, we argue that platforms tend to legitimise some forms of unpaid labour time to the extent that workers assume them to be non-working time. On the other hand, we show that platform workers apply different strategies to try to include some of these forms of unpaid labour time in their final income.
Keywords: Digital platforms; Labour time; Unpaid work